ANÁLISE DA INFLUÊNCIA DOS EFEITOS DO COPING E LIDERANÇA TRANSFORMACIONAL SOBRE O TECNOESTRESSE NOS PROFISSIONAIS CONTÁBEIS - ALMEIDA, ARI RICARDO DE (2018)
The use of Information and Communication Technologies plays an increasingly preponderant role in the life and work of contemporary society. From the point of view of the individual, the Information and Communication Technologies present importance and relation with the professional satisfaction, career and personal life, as well as associate stressors to the professional environment. This study analyzed the effects of transformational leadership and coping strategies on techno-stress. The research is based on a single cross-sectional quantitative research approach. The data were analyzed through 193 questionnaires answered by professionals from several areas, including the accounting area, which allowed an analysis among groups of professionals. For the hypothesis tests of the study, the analysis of structural equations was performed. The results indicate that transformational leadership and coping strategies have no effect on the techno-stress constructs. Despite this, significant differences were found among professionals that deal with the Public Digital Bookkeeping System, with a positive effect between transformational leadership and the positive revaluation coping strategy.